Peningkatan Kapasitas Siswa dalam Bantuan Hidup dasar Sebagai Langkah Strategis Generasi Tanggap Darurat - Nian Afrian Nuari; Efa Nur Aini; Sela Dwi Prasetianing U; Prajna Paramita Dwi Nugraha; Muchlis Santoso (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The general public, including children in schools, has to be trained in Basic Life Support (BLS). The advancement of communication and information technologies has created new avenues for the delivery of important skills training, including Basic Life Support (BLS). The goal of this community service is to use blended learning to improve students' knowledge and abilities in doing BHD. Online and offline learning are combined to execute this training-based approach to community service. While the offline component consists of practice exercises and simulations, the online component features instructional videos and other materials. The participants were 35 SMK K students in Nganjuk City. Student knowledge is measured using pre-test and post-test. The results showed a significant increase in post-test scores compared to the pre-test, with the average score increasing from 74.14 to 85.551. Students' skills in carrying out BHD also increase after participating in simulations and practice. The blended learning method has proven to be effective in increasing students' understanding and ability to perform BHD. It is hoped that this training can prepare students as potential bystanders who are able to provide first aid in cases of cardiac arrest in the community.